THE EFFECT OF THE DYNAMIC TRANSFORMATION STRATEGY OF IDEAS ON THE ACHIEVEMENT OF SECOND-GRADE MIDDLE SCHOOL STUDENTS IN BIOLOGY AND THEIR MENTAL CREATIVITY (American Journal of Research in Humanities and Social Sciences, 2025)
This research aims to identify the effect of the dynamic transformation strategy of ideas on the achievement of second-grade middle school students in biology and their mental creativity. The research was applied to second-grade middle school students in Algeria Middle School for Boys affiliated with the Diwaniyah Education Directorate/Center, which was intentionally chosen to represent a field of experimentation. The research sample consisted of 49 students, and by random assignment, Section (B) was chosen as the experimental group. The first group was taught according to the dynamic transformation strategy of ideas and consisted of (24) students, and the second group was the control group, which was taught according to the traditional method, and consisted of (25) students. The two groups were rewarded in the variables (chronological age, intelligence, previous achievement, previous information test, and mental creativity test). The researcher taught the two research groups after determining the scientific material, and the first two units included: For chapters (first, second, third and fourth) of the biology book for the second intermediate grade, then the behavioural objectives for the four chapters were determined, which amounted to (198) behavioural objectives, and the teaching plans were prepared for the two experimental research groups by adopting the strategy of dynamic transformation of ideas, and the control group by the usual method, and a test map was prepared for the achievement test by means of which the question paragraphs were prepared according to the levels of the six Bloom’s classification. Depending on determining the total number of questions, which is (40) multiple-choice paragraphs with four alternatives.As for the mental creativity test, the researcher prepared it, including (30) multiple-choice test items. To verify the validity of its items (apparent), it was presented to a group of experts and specialists. After applying it to two survey samples, the difficulty coefficient, discrimination coefficient, and effectiveness of the wrong alternatives were extracted. To calculate the stability of the test, the (Kuder Richardson-20) equation was adopted if it reached (0.85). The research experiment was applied at the beginning of the study. The first semester of the academic year (2024-2025) lasted a full semester.